Trancendental Values In Pancasila As The Personality Of The Indonesian Nation (Perspective From A Muslim) - Basri Basri; Yulia Kurniaty; Johny Krisnan (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2021)
It turns out that when studied more deeply there is a match between the teachings of Islam and the values of Pancasila. On this basis, the researcher expresses the opinion that there is no reason to contradict the teachings of Islam and Pancasila. In fact, according to the researcher, the values of Pancasila are complemented by Islamic teachings and it is possible that the values of Pancasila come from Islamic teachings. Therefore, there is no need for Muslims to question Pancasila as the basic philosophy of the Indonesian nation and state. For others, when there is a reaction from Muslims, for example there is an issue to replace Pancasila with another ideology, there is no need to react excessively, because it cannot happen and be conducted by Muslims. Such an attitude is just a reaction to what happened, in which some Muslims are seen as contradicting the values of Pancasila as the personality of the Indonesian nation. This is the real problem that needs to be found at the root of the problem. Keywords: Pancasila-Personality-Nation-Indonesia